Secondary Enrichment of REE in Weathered Granite, South Bangka, Indonesia - Tampubolon, Armin; Syafri, Ildrem; Rosana, Mega Fatimah; Yuningsih, Euis Tintin (Indonesian Journal on Geoscience, 2024)
Rare earth elements (REEs) are essential materials for the manufacture of advanced technology. Secondary REE indications were found in alluvial and lateritic tin deposits within Southeast Asia Tin Belt. This study aims at the REE enrichment of weathering profiles underlain by Toboali Pluton of the main range S-type granite of this belt. Granite and weathering samples were collected and analyzed using XRF, ICP-MS/OES, XRD, SEM-EDX, and EPMA. The Chondrite-normalized REE patterns of granite in Toboali showed enrichment in REE with the highest value of 1,126 ppm. The Toboali Pluton is enriched in LREE and depleted in HREE. The enrichment of REE from the upper to lower horizon of weathering profiles was pointed out by the increase in REE values from a range of 156-188 ppm (horizon B) to 196-268 ppm (horizon C) in Toboali, and from a range of 230-330 ppm (horizon B) to 342-450 ppm (horizon C) in Air Gegas. These coincided with the presence of kaolinite with elevated REE and CeO2 in horizon C of weathering profile. Leaching test result proved that kaolinite plays a role in REE enrichment in the weathering profile through ion adsorption mechanisms in the Air Gegas. The weathering process of REE fluoro-carbonate (bastnäsite-(Ce)) and parisite-(Ce) in granite is believed to contribute in enrichment due to its high dissolution rate, which enhances kaolinite adsorption. In contrast, REE phosphates such as monazite-(Ce) and xenotime-(Y), because of their strong resistance and low solubility, are thought to be only slightly soluble, and most of these minerals remain in Toboali weathering products.